Economic Integration in the Maghreb - World Bank (Washington, DC, 2017)
This report reviews the status of Maghreb countries' economic integration with the world, with the Arab world, and within the Maghreb itself. It focuses on trade in goods and services, labor and capital flows, financial integration and cross-border infrastructure integration. It discusses the potential benefits of and key constraints to greater integration. The focus on trade liberalization with the European Union (EU) provides an opportunity for individual Maghreb countries to lock in policies that would eventually help them harmonize policies within their own region. The same argument can be made regarding accession to the World Trade Organization (WTO). The Maghreb countries would reap significant additional benefits if, in parallel to reforms undertaken to improve trade liberalization with Europe, they improved conditions for streamlined trade among themselves. There is significant potential for trade in services in the financial sector, transportation and logistics, and communications and information, among other sectors. According to some studies, comprehensive services reforms that involve increased competition and regulatory streamlining would yield benefits that are at least twice the magnitude of those achieved through tariff removal alone.